ADAPTASI PEKERJA SEKS KOMERSIAL (PSK) DALAM BERTAHAN HIDUP (STUDY KASUS DI KOTA PEKANBARU) - Sinta Okta Sovia; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Recently, the problem of prostitution in urban areas is crucial. The city government tends to displace the presence of PSK stricken suburbs or let prostitutes roam without permission localization. In Pekanbaru similar symptoms occur, localization exs teleju moved to Meridan, mostly prostitutes under the guise of massage parlors thrives in Nangka Sari Building in Pekanbaru protocol street, and semi-permanent tents on the roadside. Interesting research problems to be studied is why PSK, select survival of profession as commercial sex workers ?. The method used is qualitatively by taking 6 informants representing each of the three locations the informants to the study, that is Meridan, Payung Sekaki and Nangka Sari. Results and discussion in this study revealed that commercial sex workers (PSK) in Pekanbaru widowed women aged around 22-35 years. Less educated and come from families who can not afford. Most prostitutes in Pekanbaru ever worked with low income before finally plunging into the world of prostitution .. The majority of prostitutes in Pekanbaru practicing prostitution under the Mami as a patron with an average income of Rp 300,000 to Rp 1 million per night. Having a location wher e prostitution remains. PSK productive working days during the month is 30 days. Their time off only when menstruation and pain they are very health conscious and always use safety devices such as condoms strategies they are doing to attract customers is to exercise care and herbal drink. Adaptation they do so is either not choose select guests who come old and easy same. And the main factor that caused them to drift into prostitution this is due to economic factors and no job options . While of most of them know that this job is not true.Keywords : Prostitution, Adaptation and Social Exchange